Perawatan Komponen CVT Sepeda Motor Matik bagi Warga Desa Pemuda - Muhammad Yunus; Muhammad Rezki Fitri Putra; Taufik Abdullah Attamimi; Kurnia Dwi Artika; Bayu Agung Wicaksono; Yulima Melsipa Lingga; Jesi Yardani; Sri Muntiah Andriami; Muhamad Muhajir; Barokah Barokah; Azelia Puteri (Apik Cahaya Ilmu, 2026)
Automatic motorcycles are widely used as the primary means of transportation, making regular maintenance, particularly of the Continuously Variable Transmission (CVT) system, essential to maintain vehicle performance and extend service life. However, public knowledge regarding CVT maintenance remains limited, causing maintenance to be performed only after mechanical problems occur. This community service program aimed to improve the knowledge and basic skills of residents of Desa Pemuda in maintaining CVT components on automatic motorcycles. The program employed a service and mentoring approach consisting of lectures, demonstrations, hands-on training, and interactive discussions. The implementation included three stages: preparation, implementation, and evaluation. The results showed that all participants attended the activity until completion and demonstrated high enthusiasm throughout the program. Participants actively engaged in discussions and practical sessions while expressing positive responses toward the training methods applied. The activity provided participants with additional knowledge and practical experience in performing basic CVT maintenance, enabling them to apply simple maintenance procedures independently. Overall, the community service program successfully enhanced public awareness of the importance of periodic motorcycle maintenance to maintain vehicle performance, reduce the risk of component failure, and encourage sustainable vehicle maintenance practices.